2013
DOI: 10.1625/jcam.10.87
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Knowledge of and Attitudes regarding Complementary and Alternative Medicine among Health Care Profession Students in Japan

Abstract: The aim of this study was to evaluate and compare levels of knowledge of and attitudes toward complementary and alternative medicine (CAM) in different groups of health care profession students. Methods: The subjects of this study were 1465 students of nursing, medicine, radiologic science, laboratory science, nutrition, dentistry, oral health and welfare, and pharmaceutical science. We used a questionnaire to obtain information on knowledge, sources of information, interest, personal use, willingness to take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
2
3
1
Order By: Relevance
“…Post hoc analysis revealed that final year medical students demonstrated the highest positive attitude than pharmacy and nursing students. This is in complete contrast to studies conducted in USA [ 19 ], Japan [ 22 ] and Malaysia [ 21 ] in which nursing students had the highest positive attitude towards CAM as compared to their peers in the medical and pharmacy faculties. It is worthy to note that, in our study, no significant difference in attitude towards CAM existed between final year pharmacy and nursing students.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Post hoc analysis revealed that final year medical students demonstrated the highest positive attitude than pharmacy and nursing students. This is in complete contrast to studies conducted in USA [ 19 ], Japan [ 22 ] and Malaysia [ 21 ] in which nursing students had the highest positive attitude towards CAM as compared to their peers in the medical and pharmacy faculties. It is worthy to note that, in our study, no significant difference in attitude towards CAM existed between final year pharmacy and nursing students.…”
Section: Discussioncontrasting
confidence: 96%
“…This hypothesis is supported by the fact that most students in all three study groups considered the CAM modalities they have used to be effective and less harmful. Similar observations were reported among health professional students in Japan [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, the national nursing education policy recently issued in China has made it explicit that EBP should be one of the basic capabilities for nursing undergraduates (including TCM nursing majors), and that TCM nursing discipline can be advanced through the implementation of EBP ( 60 ). Takata et al also suggest that nurses who have been educated about the scientific evidence for CAM may play critical roles in advising on CAM, including its benefits and risks, as well as in supporting the self-care in response to patients' clinical requirements ( 63 ). Meanwhile, these roles would also strengthen the relationship between nurses and their patients, which, in turn, enhance the professional motivation of nurses ( 63 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, it has shown that perception of CAM therapies differed depending on the groups of health care profession students 18) . To our knowledge, gender differences in attitudes toward and knowledge of CAM among health care profession students have not been evaluated in Japan.…”
Section: Introductionmentioning
confidence: 91%